The Influence of STEM: Integrated PjBL Learning Models on Students' Mathematical Creative Thinking Abilities Examined from a Metacognitive Perspective - Purwati, Heni; ., Sudargo; Indiati, Intan; Melly Savira, Agnes (KnE Social Sciences, 2024)
The STEM-integrated PjBL learning model is one solution to enhance students’ creative mathematical thinking skills. Efforts to maximize students’ mathematical creative thinking abilities involve using a metacognitive approach. This research aims to (1) determine the effect of the STEM-integrated PjBL learning model on students’ mathematical creative thinking abilities in terms of metacognition and (2) investigate the interaction between the learning models and students’ metacognition levels (high, medium, and low) on students’ mathematical creative thinking abilities between the experimental and control classes. The population in this study consisted of all eighth-grade students at SMP Negeri 6 Jepara for the 2022/2023 academic year. The samples for this research were selected from class VIII-E and class VIII-G using a cluster random sampling technique. The research design employed was the posttestonly control group design. Data collection in the research included metacognitive questionnaires, written creative thinking tests, and documentation. Data were analyzed using a two-way ANOVA test followed by the Scheffe test. The results of the research indicate that (1) there is an influence of the STEM-integrated PjBL learning model on students’ mathematical creative thinking abilities in terms of metacognition, and (2) there is an interaction between the learning model and students’ metacognition levels on mathematical creative thinking abilities. Students who received STEM-integrated PjBL learning showed better results in terms of mathematical creative thinking abilities when compared to students who underwent conventional learning. Keywords: STEM integrated PjBL, think creatively, metacognitive